Method of dynamic integrity measurement for VMM based on adjacency data - Tao WU; Qiu-song YANG; Ye-ping HE (Tongxin xuebao)
Due to its high privilege and complicated runtime memory,dynamic integrity measurement for VMM (virtual machine monitor) was always a great difficulty in the current study.An innovative method based on the adjacency data was proposed,which used a neighbor as the host of a measurement module.According to an integrity model in memory page granularity and a new improved measurement algorithm,dynamic integrity measurement for VMM was imple-mented.Experimental data shows it could detect the integrity broken accurately,only causing a moderate performance loss for computing intensive tasks.